지하수 보전가치 추정에 관한 연구 - 신효중 (한국농촌경제연구원, 2011)
The purpose of this research is to estimate the conservation values of Jeju groundwater by using the double bounded contingent valuation (DBCV) method, which is one of main methodologies to tackle non-use values of public goods. Jeju groundwater has been at the center of dispute over its development and conservation in recent years. The Samdasoo company, which extracts groundwater from Jeju Island and which occupies over 40% market share of the domestic water market, has a plan to expand the amount of groundwater extraction, while the conservation side continuously points out that the conservation value of Jeju groundwater is also as important as its market value now. With respect to this issue, the Dong-seo Research Group conducted a face-to-face survey (DBCV questionnaire) of 600 Jeju residents from July 13 to August 5, 2010. The result of the one-off conservation fund payment mechanism applied here found that the amount of additional WTP is ￦11,023 on average per household. The expanded total conservation benefit to all 219,771 households in Jeju is about ￦2.4billion. The result shows that ￦11,023 of WTP is at the equivalent level to its use value, the monthly tap water cost of ￦12,530 per household in 2008, and that the benefit of conserving groundwater in Jeju is no less than the present market value.
Keywords: 이중양분선택형 조건부가치측정법; 지하수; 보전가치; double bounded contingent valuation; groundwater; conservation value